2004
DOI: 10.1164/rccm.200312-1663oc
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Regional Lung Perfusion by Nitric Oxide

Abstract: Improved oxygenation has previously been shown in patients with acute lung injury when ventilated in prone position. We hypothesized that this was due to higher regional production of nitric oxide in dorsocaudal lung regions. We measured nitric oxide synthase mRNA expression and nitric oxide production by citrulline assay in ventral and dorsal lung tissue from patients. In volunteers, regional lung perfusion in prone and supine postures was assessed by single photon emission computed tomography using (99m)Tc m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…Pulmonary vascular endothelium production of nitric oxide is substantially greater in the dorsal versus the ventral lung. 61 Also, because more lung tissue resides in the dorsal plane, there is more pulmonary vasculature available and a higher capacitance to accommodate cardiac output compared with the ventral lung, regardless of gravitational forces. Therefore, regional pulmonary vascular resistance would remain lower in the dorsal lung.…”
Section: Pulmonary Perfusion In Ppmentioning
confidence: 99%
“…Pulmonary vascular endothelium production of nitric oxide is substantially greater in the dorsal versus the ventral lung. 61 Also, because more lung tissue resides in the dorsal plane, there is more pulmonary vasculature available and a higher capacitance to accommodate cardiac output compared with the ventral lung, regardless of gravitational forces. Therefore, regional pulmonary vascular resistance would remain lower in the dorsal lung.…”
Section: Pulmonary Perfusion In Ppmentioning
confidence: 99%
“…In a recent study, Rimeika et al (70) used SPECT to demonstrate that local production of nitric oxide (NO) influences the distribution of lung blood flood in normal subjects. In the supine posture inhibition of NO synthase caused a redistribution of blood flow from dorsal to ventral regions.…”
Section: Active Regulation Of Lung Blood Flowmentioning
confidence: 99%
“…Furthermore, if NO was formed preferentially in dorsal lung as suggested by prior research (Pelletier et al, 1998 andRimeika et al, 2004), redistribution of Q to ventral lung should result with blockage of cNOS. However, we found a small but significant redistribution of Q from ventral to dorsal regions, Figure 10, contrary to what would be expected (Pelletier et al, 1998, Rimeika et al, 2004, Rimeika et al, 2006. There was no difference in total V/Q heterogeneity as a result of this small redistribution, which was also supported by a preserved PaO 2 and (A-a)O 2 difference.…”
Section: Minimal Change In V/q Distributions By L-namementioning
confidence: 84%
“…Beck and Rehder (Beck and Rehder, 1986) showed that vascular conductance was higher in dorsal lung in dogs in the supine, lateral and head-up positions, but the prone position was not examined. Evidence for uneven formation of NO in the lung was provided by in vitro studies showing greater eNOS activity in dorsal than in ventral lung regions in animals and humans, and similar regional differences in NO-mediated vasorelaxation in equine and porcine pulmonary arteries (Pelletier et al, 1998, Rimeika 2004et al, Rimeika et al, 2006. Rimeika et al (Rimeika et al, 2004) tried to confirm this by examining humans with SPECT in the prone and supine positions after inhibition of NO production.…”
Section: Endogenous No and V/q Matching Paper Iv: Inhibition Of Constmentioning
confidence: 99%
See 1 more Smart Citation